Depressive symptoms and adipokines in women: Study of women's health across the nation. (November 2018) - Everson-Rose, Susan A.; Clark, Cari J.; Wang, Qi; Guo, Hongfei; Mancuso, Peter; Kravitz, Howard M.; Bromberger, Joyce T.
Highlights: Depressive symptoms are inversely related to adiponectin, an anti-inflammatory, anti-atherogenic secretory protein derived from fat cells. Compared to women with low CES-D scores, those with high CES-D scores had 7% lower adiponectin levels at baseline and 11% lower levels over 5 years. Depressive symptoms have a dampening effect on adiponectin levels, but do not differentially affect rate of change in adiponectin over time. Depressive symptoms and leptin were not related to each other. Abstract: Small clinical studies suggest depression is associated with alterations in adiponectin and leptin, adipocyte-derived secretory proteins involved in metabolic regulation; however, longitudinal data on these association are lacking. This study examined cross-sectional and longitudinal associations of depressive symptoms and major depressive disorder (MDD) with adiponectin and leptin in healthy middle-aged women (mean (SD) age, 45.6 (2.5) years). Cross-sectional analyses included 575 women with baseline adipokine data; longitudinal analyses included 262 women with 2–4 adipokine measurements over 5 years. The 20-item Center for Epidemiologic Studies Depression scale (CES-D) was used to assess depressive symptoms; history of MDD was determined by the Structured Clinical Interview for DSM-IV. Adipokines were assayed from stored serum specimens; values were log-transformed for analyses. Linear and repeated measure random effects regression models evaluated associations of baseline CES-D scores with baseline adipokine concentrations and changes over time, respectively. Secondary analyses evaluated the relation of MDD history with adipokine concentrations. Mean (SD) baseline concentrations of adiponectin and leptin were 9.90 (4.92) μg/mL and 27.02 (20.06) ng/mL; both increased over time ( p  < .0001). CES-D scores were associated with lower adiponectin at baseline (per 1-SD: estimate=-0.04, SE=.02, p= .03) and over time (per 1-SD: estimate=-0.055, SE = .024, p= .02). Associations were unchanged in risk factor-adjusted models. Women with elevated CES-D scores (≥16) had 6.9% (95% CI: −1.1%, 14.3%; p  = .089) lower median adiponectin at baseline and 11.5% (95% CI: 1.5%, 20.4%, p  = .025) lower median adiponectin over time in adjusted models, compared to women with CES-D<16. Rate of change in adipokines did not vary by baseline depressive symptoms or MDD history. Depressive symptoms and MDD history were unrelated to leptin. In women at midlife, depressive symptoms are associated with lower adiponectin, a critical anti-inflammatory biomarker involved in metabolic and cardiovascular conditions.